The Limits of Demonstration Elections - Magno, Alexander R. (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Numerous Third World dictatorships have resorted to the cynical use of the electoral process to consolidate tyranny rather than advance democracy, deodorize the institutionalization of state terror, outmaneuver the popular movements or--in the case of US client regimes--appease occasional American breastbeating on the future of democracy and the fate of human rights.